Correlation Between Skin and Affected Organs in 52 Sclerodermic Patients Followed in a Diseases Management Team: Development of a Risk Prediction Model of Organ-Specific Complications - Cozzani, Emanuele; Muracchioli, Andrea; Murdaca, Giuseppe; Beccalli, Mirko; Caprioli, Simone; Zentilin, Patrizia; Ameri, Pietro; Grosso, Marco; Russo, Rodolfo; Carmisciano, Luca; Parodi, Aurora (Frontiers in Immunology, 2021)
Objective: to identify the existence of a correlation among the various organs affected, focusing primarily on immuno-dermatological aspects, and to create a risk prediction model of organ-specific complications. Material and Methods: Fifty-two patients with stable scleroderma, followed between 2015 and 2019, were evaluated through an extensive multidisciplinary evaluation in the last year. Results: Patients with lung involvement presented a worse degree of skin fibrosis than patients without it (p<0.001). No relationship was observed for the heart, kidney and esophagus. Patients with pulmonary involvement had a lower pressure of the low esophagus sphincter and a higher Warrick score than patients without it (p<0.05). Age was significatively higher in patients with kidney involvement. Diffuse scleroderma patients had a worse pulmonary impairment than limited scleroderma patients (p<0.05). The manometric ''sclerodermic'' pattern was observed to be the most frequent (55.6%, p< 0.05) in dcSSc patients while the sclerodermic and normotonic pattern were equally represented (41.2% and 32.4% respectively, p<0.05) in lcSSc patients. When compared to the negative serological groups, anti-Scl-70 positive patients presented a worse lung involvement while anti-centromere patients presented a better lung outcome (p<0.05). PM-Scl 100/75 positive patients presented mostly a pulmonary fibrotic pattern (p<0.05) and, also, hearth complications were more likely associated with anti PM-Scl 100/75 positivity (p<0.05). The risk prediction model for organ-specific complications had an accuracy of 84.4% (95%CI 78, 89) in complication-site prediction, AUC of 0.871, 86% of sensitivity and 83% of specificity, Cohen’s Kappa (k) of 0.68. Conclusions: Out of all the organs studied, the skin is the one that correlates with the lung. Patients with a diffuse form of disease presented more frequently the anti Scl-70 antibody and had a worse lung and esophageal involvement (scleroderma pattern) than the negative group. Conversely, patients with limited disease presented all positive for the anti-centromere antibody with a better lung involvement than the negative group, without any difference among the esophageal manometric pattern. Anti PM-Scl 100/75 antibody patients were associated with pulmonary fibrosis and presented cardiac involvement. The model created has demonstrated excellent values of sensitivity, specificity and accuracy, but further studies are needed for validation.